Are tinnitus burden and tinnitus exacerbation after cochlear implantation influenced by insertion technique, array dislocation, and intracochlear trauma? - Everad, F.; Beck, R. L.; Aschendorff, A.; Rauch, A. K.; Fries, Leonie; Arndt, S.; Ketterer, M. C. (Frontiers in Neurology, 2024)
Introduction Although numerous studies suggest that cochlear implantation (CI) generally alleviates the overall burden of tinnitus, certain patients experience tinnitus exacerbation following CI. The exact cause of this exacerbation is still uncertain. This prospective study aimed to investigate whether cochlear trauma, resulting from scalar dislocation of the electrode array, affected postoperative tinnitus intensity, tinnitus burden, and speech perception. Additionally, the influence of CI insertion technique, insertion depth, insertion angle, and cochlear morphology on postoperative tinnitus was assessed. Methods We evaluated 66 CI recipients preoperatively at 2 days, 4 weeks, and 12- and 24-months following surgery. Digital volume tomography was employed to document scalar position, insertion depth, and cochlear morphology postoperatively. Speech perception was analyzed using Freiburg monosyllables. The tinnitus burden was evaluated using the tinnitus questionnaire, while the tinnitus intensity was quantified using a visual analog scale. Results Study results pertaining to tinnitus intensity and burden did not reveal a significant difference in elevation regarding scalar position and dislocation after CI surgery compared to preoperative tinnitus levels. However, dislocation was only identified in four patients, and scala vestibuli insertions were observed in two patients. Comparing preoperative and 1-year postoperative outcomes, CI was noted to substantially reduce the tinnitus burden. When the speech processor was worn, the tinnitus intensity was significantly diminished. In comparison to round window (RW) insertion, the insertion technique cochleostomy (CS) did not exhibit a significant difference or a trend toward increased tinnitus intensity. Conclusion This study demonstrates that CI significantly decreases the tinnitus burden. The observation implies that the electrical stimulation of the auditory pathway, facilitated by wearing the speech processor, significantly reduced the tinnitus intensity. The incidence of dislocations and scala vestibuli insertions has declined to the extent that it is no longer feasible to formulate statistically significant conclusions.